Analisis Attitude towards the Environment pada Siswa Sekolah Adiwiyata dan Sekolah Non-Adiwiyata - Larashati Larashati; Sukarmin; Annisa Nur Khasanah (Jurnal Penelitian Pendidikan IPA, 2022)
Environmental protection and preservation are in the hands of citizens and students are the future of the nation, so it is very important to assess or measure the attitude towards the environment owned by students. The aims of this research are to: (1) analyze the attitude towards the environment in students of Adiwiyata and Non-Adiwiyata schools on EBSS (Environmental Behavior Sub Scale), EOSS (Environmental Opinion Sub Scale), and EESS (Environmental Emotion Sub Scale); and (2) analyze the attitude towards the environment in students of Adiwiyata and Non-Adiwiyata schools. The research method used is a mixed method with a sequential explanatory design. Data analysis used descriptive statistics and inferential statistics with independent samples t-test. The results showed that there were significant differences in attitudes towards the environment between Adiwiyata and Non-Adiwiyata school students on EBSS, EOSS, and EESS with the significance probability of 0.007, 0.000, and 0.025 respectively. The research results generally showed that there were significant differences in attitudes towards the environment between Adiwiyata and Non-Adiwiyata school students with a significant probability of 0.000. The conclusion of this research is significant differences in attitudes towards the environment between Adiwiyata and Non-Adiwiyata school students both in EBSS, EOSS, EESS, and overall.